Coronary artery calcification on routine CT has prognostic and treatment implications for all ages. Issue 6 (June 2023) - Graby, J.; Soto-Hernaez, J.; Murphy, D.; Oldman, J.L.A.F.; Burnett, T.A.; Charters, P.F.P.; Barrishi, A.; Thanaraaj, T.; Masterman, B.J.; Khavandi, A.; Rodrigues, J.C.L.
Abstract : Aims: Guidelines have recommended reporting coronary artery calcification (CAC) if present on chest CT imaging regardless of indication. This study assessed CAC prevalence, prognosis and the potential clinical impact of its reporting. Methods: We performed a single-centre retrospective analysis (January-December 2015) of 1400 chest CTs (200 consecutive within each age group: <40, 40-49, 50-59, 60-69, 70-79, 80-89, ≥90). CTs were re-reviewed for CAC presence and severity and excluded if prior coronary intervention. Comorbidities, statin prescription and clinical outcomes (myocardial infarction [MI], stroke, all-cause mortality) were recorded. The impact of reporting CAC was assessed against pre-existing statin prescriptions. Results: 1343 patients were included (mean age 63±20 years, 56% female). Inter- and intra-observer variability for CAC presence at re-review was almost perfect ( κ 0.89, p < 0.001; κ 0.90, p < 0.001) and for CAC grading was substantial and almost perfect ( κ 0.68, p < 0.001; κ 0.91, p < 0.001). CAC was observed in 729/1343 (54%), more frequently in males ( p < 0.001) and rising age ( p < 0.001). A high proportion of patients with CAC in all age groups had no prior statin prescription (range: 42% [80-89] to 100% [<40]). The 'number needed to report' CAC presence to potentially impact management across all ages was 2. 689 (51%) patients died (median follow-up 74-months). CAC presence was associated with risk of MI, stroke and all-cause mortality ( p < 0.001). After adjusting for confounders, severe calcification predicted risk of all-cause mortality (HR 1.8 [1.2-2.5], p = 0.002). Conclusion: Grading of CAC was reproducible, and although prevalence rose with age, prognostic and treatment implications were maintained in all ages.